Dietary Interventions and Nutritional Factors in the Prevention of Pediatric Asthma - Trambusti, Irene; Nuzzi, Giulia; Costagliola, Giorgio; Verduci, Elvira; D'Auria, Enza; Peroni, Diego G.; Comberiati, Pasquale (Frontiers in Pediatrics, 2020)
Asthma is the most frequent chronic disease in children, and its pathogenesis involves genetic, epigenetic and environmental factors. The rapid rise in the prevalence of asthma registered over the last few decades has stressed the need to identify the environmental and modifiable factors associated with the development of the disease. In particular, there is increasing interest in the role of modifiable nutritional factors specific to both the prenatal and post-natal early life as, during this time, the immune system is particularly vulnerable to exogenous interferences. Several dietary factors, including maternal diet during pregnancy, the duration of breastfeeding, the use of special milk formulas, the timing of the introduction of complementary foods, and prenatal and early life supplementation with vitamins and probiotics/prebiotics, have been addressed as potential targets for the prevention of asthma. In this review, we outline recent findings on the potential role of prenatal and perinatal dietary and nutritional interventions for the primary prevention of pediatric asthma. Moreover, we addressed unmet needs and areas for future research in the prevention of childhood-onset asthma.